JORNALISMO INTERNACIONAL E AS NOTÍCIAS DO BRASIL Práticas de produção de conteúdo, enquadramentos e valores-notícia - Almeida , Francisco Antonio Oliveira de (2018)
This research has international journalism and Brazilian news in the world press as its theme and, as its object, the country’s coverage by foreign agencies and newspapers in the year of 2016. It is intended to investigate how this coverage is seen in foreign newspapers, generated by international news agencies, considering the dynamics of production in international journalism in a contemporary context, the news criteria and the complexity of journalistic routines. The news contribute to the construction of a social and cultural reality and agencies, in turn, generate a great share of international news, which certifies the relevance and actuality of the research. Methodologically, a descriptive approach uses quantitative and qualitative mechanisms, such as bibliographic research. Add to that the use of documental research and, moreover, the content analysis in articles published, in 2016, in the website of four foreign newspapers (El País, Le Fígaro, The Guardian and The New York Times), having as source the news agencies Reuters and Associated Press. The benchmarks are constituted around three theoretical axes: the first one focused in international journalism; the second, in journalism productive routines and the third, in news criteria and frameworks regarding Brazil. Great relevance to this work, even having been released in 1983, is given to the document “One world and many voices: communication and information in our time”, which presents results of a study on communication issues in relationships among countries. Commissioned by UNESCO, this text has become worldly known as the McBride report, given that the Irish man, Sean McBride, has coordinated the team. The results suggest that: a) in the news criteria hierarchy, there is emphasis on economic coverage, highlighting the agenda on the political-economic crisis and corruption; b) in both international agencies journalists’ routines, there is emphasis on monitoring content which is produced by national vehicles for communication and on the enquiries to fonts, specially, official ones; in the background, anonymous sources, national vehicles, witnesses and, at last, what is known as counterpoint; c) the most highlighted news criteria are actuality, dramatization and notoriety.